Islamic worldview and its implications on the teaching of microeconomics - Imon, Riasat Amin; Barom, Mohd Nizam (Centre for Islamic Economics, Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia and International Institute of Islamic Thought, 2024)
This chapter provides an essential discussion on the Islamic worldview and its implications on the teaching of microeconomics. In Islam, the worldly life must be related in a profound and inseparable way to the hereafter, where the latter has the ultimate and final significance. The universe and all of God’s creations are signs of His power and wisdom, and the worldly resources are held in trust to individuals as trustees- vicegerent of God in this world. individual is called to seek the bounties of God in this world and uses the resources to achieve prosperity on earth, provided that they are in line with the will of God- enjoining what is good, forbidding what is wrong, establishing justice ('adl) and promoting beneficence (ihsan). This worldview of Islam in turn, shapes the economic outlook of the Muslims with regard to their economic decisions. This necessitates individuals to harmonise material wellbeing with moral-spiritual values, which is the key to attain the ultimate happiness (falah), in this world and in the Hereafter. This is totally in opposition to the concept of secularism and materialism, which are the core values in the mainstream economics. The chapter subsequently discusses the implications of the Islamic worldview on a number of important economic concepts, such as the concept of scarcity of resources and human well-being.